The Integration of the Iqra Paradigm and the Value of Tabayyun: Strengthening Character-Based Digital Literacy to Counter Misinformation on Social Media - Fahriah Fahriah; Hidayat Ma'ruf; Husul Yaqin; Hamdan Hamdan; Hamrani Hamrani (Interdisciplinary Explorations in Research Journal, 2026)
The massive spread of hoaxes and disinformation on social media in the digital age poses serious challenges to literacy, communication ethics, and religious authority. Conventional models of digital literacy are considered inadequate because they focus more on technical aspects and pay less attention to character development and spiritual values. This study aims to reconstruct the Iqra paradigm and the value of Tabayyun as a model of Islamic digital literacy to address disinformation in cyberspace. The study employs a qualitative approach using library research. The primary data sources are drawn from the Qur’an, specifically Surah Al-‘Alaq, verses 1–5, and Surah Al-Hujurat, verse 6, as well as various exegetical works and studies on digital literacy. Data analysis was conducted using a thematic exegesis (tafsir maudhu’i) approach and thematic analysis. The results indicate that the Iqra’ paradigm serves as the foundation for critical thinking in understanding and analyzing information, while Tabayyun functions as a verification mechanism through the validation of sources (sanad), content accuracy (dhabt), and consideration of social impact (maslahah). The integration of these two concepts forms a character-based digital literacy model that emphasizes the values of shidq, amanah, adl, and iffah in digital behavior. This study recommends strengthening digital literacy in Islamic Religious Education through curriculum reorientation, enhancing teachers’ digital competencies, and building an ethical and responsible digital ecosystem.